Estudo sobre contratos entre investidores e gestores de venture capital no Brasil - Ramirez Coelho, Gabriel (2007)
During the last two decades, the private equity and venture capital industry role in Brazil has significantly increased, with the expansion of resources under management and number of transactions. At the same time, the degree of sophistication of its legal environment and contractual structures has increased to cope with the particularly intense agency problems present due to (i) low liquidity of assets; (ii) the long term nature of contracts; (iii) the potentially huge asymmetry of information between investors and managers. This dissertation explores the presence of restrictions to the venture capital fund managers’ activities; and shows that there is a strong relation between the number of restrictions and the intensity of agency problems, but inconclusive evidence relating the restrictions to demand conditions.